2021
DOI: 10.1088/1755-1315/637/1/012095
|View full text |Cite
|
Sign up to set email alerts
|

Improvement growth of sapodilla (Achras zapota L.) by chitosan

Abstract: Indonesia’s palm oil production needs to be developed; generative sapodilla cultivation has a very long growth. The effort that can be done to increase the growth of sapodilla seeds for the provision of quality seedlings. Giving chitosan expected to increase the growth of sapodilla seeds because there is chitosan content that accelerate plant growth, and age planting shorter. The aim of this research is to know the concentration and time of spraying of chitosan to be applied to generative sapodilla seeds. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Putri et al (2022) reported the similarity of chromosomes in several varieties of Nephelium lappaceum. This result is supported by Yuniastuti et al (2018) that in general the shape of chromosomes has similarities even within one family. The shape of the chromosomes can also be influenced by the translucency of the chromosomes when they are killed.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Putri et al (2022) reported the similarity of chromosomes in several varieties of Nephelium lappaceum. This result is supported by Yuniastuti et al (2018) that in general the shape of chromosomes has similarities even within one family. The shape of the chromosomes can also be influenced by the translucency of the chromosomes when they are killed.…”
Section: Discussionsupporting
confidence: 56%
“…The results showed that the three types of matoa (green, yellow, and red) had the same number of chromosomes, namely 22 chromosomes with 11 pairs. According to Yuniastuti et al (2018), the number of chromosomes in one species generally has the same number, shape, and size. The chromosome pairs are known as homologous or diploid (2n) chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the figure 1, it can be seen that in the first and second months the K3W2 treatment gave the fastest height growth response, so it can be said that the use of chitosan at a concentration of 4% and watering in the afternoon can encourage the growth of apical meristems, especially at the beginning of the seedling phase. The application of chitosan at the right time and in the right way will encourage the IOP Publishing doi:10.1088/1755-1315/1018/1/012022 3 growth of apical meristems [6]. In the third month, all treatments gave good results when compared to the control, this indicates that chitosan affects plant growth at the beginning of the phase.…”
Section: Figure 1 Graph Of Plant Height Growth Gradientmentioning
confidence: 91%
“…According to the results, there are similarities between each pair from each variety. Ideograms can help to clearly show the shape and size of one set of chromosomes (Yuniastuti et al 2018). The karyotype of each individual of one species generally has the same shape and size, but this does not rule out differences.…”
Section: Karyotype Chromosomesmentioning
confidence: 99%